2020
DOI: 10.21203/rs.3.rs-21175/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil origin and plant genotype structure distinct microbiome compartments in the model legume Medicago truncatula

Abstract: Background: Understanding the genetic and environmental factors that structure plant microbiomes is necessary for leveraging these interactions to address critical needs in agriculture, conservation, and sustainability. Legumes, which form root nodule symbioses with nitrogen-fixing rhizobia, have served as model plants for understanding the genetics and evolution of beneficial plant-microbe interactions for decades, and thus have added value as models of plant-microbiome interactions. Here we use a common gard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 101 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…To further investigate the ecological relevance of our NREs, we asked whether our three ASVs of interest, representing the three inoculum strains, could also be detected among amplicon data from a separate study of the leaf, root, and nodule endophytes of M. truncatula endophytes grown in native field soil (Brown et al 2020). Aligning our ASVs of interest against the 50 most abundant sequences generated by Brown et al (2020) revealed imperfect but numerous alignments to taxa in their study (Table S10). The best alignment of ASV1 was OTU00001, an “ Ensifer ” bacterium (now reclassified as Sinorhizobium ) that was found to be a significant nodule endophyte in the Brown et al (2020) study, at 99% identity with 92% coverage of the OTU (Table S10).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To further investigate the ecological relevance of our NREs, we asked whether our three ASVs of interest, representing the three inoculum strains, could also be detected among amplicon data from a separate study of the leaf, root, and nodule endophytes of M. truncatula endophytes grown in native field soil (Brown et al 2020). Aligning our ASVs of interest against the 50 most abundant sequences generated by Brown et al (2020) revealed imperfect but numerous alignments to taxa in their study (Table S10). The best alignment of ASV1 was OTU00001, an “ Ensifer ” bacterium (now reclassified as Sinorhizobium ) that was found to be a significant nodule endophyte in the Brown et al (2020) study, at 99% identity with 92% coverage of the OTU (Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…The Pseudomonas and Bacillus NRE strains studied here were originally isolated from nodules of M. truncatula grown in soils collected from its natural range. By comparing our sequencing results to those of another study that grew M. truncatula in such soils (Brown et al 2020), we found OTUs representing taxa closely related to Bacillus sp.…”
Section: Identifying Potential Pseudomonas and Bacillus Nres Elsewherementioning
confidence: 88%
See 3 more Smart Citations